2009
DOI: 10.1016/s1542-0124(12)70185-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Defenses in the ocular surface

Abstract: The human eye is subjected constantly to oxidative stress due to daily exposure to sunlight, high metabolic activities, and oxygen tension. Reactive oxygen species generated from environmental insults and pathological conditions render the human eye particularly vulnerable to oxidative damage. The ocular surface composed of the tear film, the cornea, and the aqueous humor forms the first physical and biochemical barrier of the eye and plays a pivotal role in combating free radicals. These ocular compartments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 106 publications
(119 reference statements)
2
116
0
3
Order By: Relevance
“…In this context, ALDH1A1 and ALDH3A1 (also respectively referred to as lens and corneal crystallins) are the isozymes that defend ocular surface tissues from reactive oxygen species (Estey et al, 2007;Chen et al, 2009). In addition, they maintain the integrity of the lens and cornea through nonenzymatic activities, including direct absorption of harmful UV radiation or serving as chaperones to prevent aggregation of misfolded proteins .…”
Section: A Enzymatic Functions Of Aldehyde Dehydrogenase Isozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, ALDH1A1 and ALDH3A1 (also respectively referred to as lens and corneal crystallins) are the isozymes that defend ocular surface tissues from reactive oxygen species (Estey et al, 2007;Chen et al, 2009). In addition, they maintain the integrity of the lens and cornea through nonenzymatic activities, including direct absorption of harmful UV radiation or serving as chaperones to prevent aggregation of misfolded proteins .…”
Section: A Enzymatic Functions Of Aldehyde Dehydrogenase Isozymesmentioning
confidence: 99%
“…Increased ALDH activity, however, has been found to interfere with certain chemotherapeutic treatments (Slá dek, 1999;Jelski et al, 2007;Tanei et al, 2009;Deng et al, 2010). In addition, ALDHs can act as esterases (Blackwell et al, 1983;Yoshida et al, 1998) and also perform nonenzymatic functions, such as reducing osmotic stress in plants, binding to macromolecules (such as androgen and cholesterol) and protecting the mammalian cornea from UV exposure (Estey et al, 2007;Chen et al, 2009). Genetic polymorphisms of ALDH isozymes that result in diminished enzymatic activity are associated with several clinical disease states, including Sjögren-Larsson syndrome, Type 2 hyperprolinemia, pyridoxine-dependent seizures, hyperammonemia, ␥-hydroxybutyric aciduria, and alcoholic liver disease (Marchitti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Bei einem Überschuss an Oxidantien ist die Kapazität allerdings erschöpft, und die Schutzfunktion kann nicht aufrecht erhalten werden [13,14]. Man vermutet, dass dadurch zahlreiche Erkrankungen des Sehapparats, wie Katarakt, altersbedingte Makuladegeneration, aber auch das Trockene Auge ausgelöst werden können [15][16][17][18].…”
Section: Oxidativer Stress Als Ursache Für Die Entstehung Diverser Krunclassified
“…Oxidative mechanisms contribute to the development of many visionimpairing conditions of the ocular surface. 40,41 Studies on mucus have shown the mechanism of action of NAC is the reduction of disulfide bonds (S -S) to sulfhydryl bonds (-SH) 42 within the glycoprotein mucin, in turn disrupting crosslinking between monomers. 41 Similarly, we postulate that the use of an antioxidant that reduces mucin oligomerization will have a downstream effect on protein deposition on the contact lens.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Studies on mucus have shown the mechanism of action of NAC is the reduction of disulfide bonds (S -S) to sulfhydryl bonds (-SH) 42 within the glycoprotein mucin, in turn disrupting crosslinking between monomers. 41 Similarly, we postulate that the use of an antioxidant that reduces mucin oligomerization will have a downstream effect on protein deposition on the contact lens. Furthermore, this study demonstrates that the use of topical NAC can be linked to the improvement in protein deposit-related symptoms, such as decreased visual acuity and comfort.…”
Section: Introductionmentioning
confidence: 99%